2013
DOI: 10.1016/j.ijid.2013.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Malignant diseases and mortality in blood donors infected with human T-lymphotropic virus type 1 in Israel

Abstract: We found a high rate of malignant diseases among HTLV-1-infected blood donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Similarly, our study determined that patients with either HTLV-1 or HTLV-2 infection and a cancer diagnosis had worse OS than patients with cancer alone. Studies of PLHTLV have implicated HTLV-1 in various cancers and its promotion of cancer progression ( Arisawa et al, 2003 ; Stienlauf et al, 2013 ; Dias et al, 2018 ; Du et al, 2019 ). Indeed, our findings are consistent with recent retrospective cohort data from Valcarcel et al showing that PLHTLV with concomitant non-ATL cancer diagnoses, excluding diffuse large B-cell lymphoma (DLBCL), had worse survival outcomes than those reported in the general Latin American population ( Valcarcel et al, 2022 , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, our study determined that patients with either HTLV-1 or HTLV-2 infection and a cancer diagnosis had worse OS than patients with cancer alone. Studies of PLHTLV have implicated HTLV-1 in various cancers and its promotion of cancer progression ( Arisawa et al, 2003 ; Stienlauf et al, 2013 ; Dias et al, 2018 ; Du et al, 2019 ). Indeed, our findings are consistent with recent retrospective cohort data from Valcarcel et al showing that PLHTLV with concomitant non-ATL cancer diagnoses, excluding diffuse large B-cell lymphoma (DLBCL), had worse survival outcomes than those reported in the general Latin American population ( Valcarcel et al, 2022 , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…A prospective cohort study in Nagasaki identified 1997 HTLV-1+ patients and found that carrier status was associated with increased risk of all-cause mortality and development of non-neoplastic diseases and heart disease ( Iwata et al, 1994 ). Another retrospective study in Israel found high incidences of malignancies among PLHTLV, including ATL, mycosis fungoides, cervical carcinoma, and transitional cell carcinoma ( Stienlauf et al, 2013 ). Few large studies have been conducted in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported in all HTLV-1 endemic areas, but incidence seems to be higher in certain areas, such as southern Japan. Its incidence is estimated in some populations to be approximately 0.37 per 100 HTLV-1 carrier-years [90], whereas other authors estimate an incidence of 3% among HTLV-1-infected patients. Some studies have hypothesized that several risk factors may be present in the development of ATLL in asymptomatic carriers, such as smoking, infection during childhood, presence of some HLA serotypes and high anti-HTLV antibodies titers, but the only risk factors proven to be clearly related to disease occurrence are high proviral load, advanced age and family history of ATLL [59].…”
Section: Pathogenesis and Clinical Featuresmentioning
confidence: 95%
“…Epidemiological and molecular studies demonstrate a credible association between HTLV-1 infection and ATLL, which is a rare and aggressive T-cell cancer found most commonly in areas where HTLV-1 is endemic, the risk of developing ATLL was greater with higher proviral load (the percentage of circulating CD4 T cells with integrated viral DNA) or higher anti-HTLV-1 antibody levels. Prospective studies and detection of a monoclonal insertion site of HTLV-1 DNA in tumours indicate that infection precedes diagnosis of ATLL (Biswas et al, 2010;IARC, 2012;Stienlauf et al, 2013). Most HTLV-1infected individuals are lifelong symptomless carriers [7] only 2% to 5% of infected people develop diseases related to the virus [8].…”
Section: Introductionmentioning
confidence: 99%